2007
DOI: 10.4049/jimmunol.179.7.4626
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 and CD4+CD25+ Regulatory T Cells Inhibit Protective Immunity to Filarial Parasites In Vivo

Abstract: The T cell coinhibitory receptor CTLA-4 has been implicated in the down-regulation of T cell function that is a quintessential feature of chronic human filarial infections. In a laboratory model of filariasis, Litomosoides sigmodontis infection of susceptible BALB/c mice, we have previously shown that susceptibility is linked both to a CD4+CD25+ regulatory T (Treg) cell response, and to the development of hyporesponsive CD4+ T cells at the infection site, the pleural cavity. We now provide evidence that L. sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
109
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 59 publications
10
109
0
3
Order By: Relevance
“…The interference with regulatory T cell function in L. sigmodontis-infected BALB/c mice led to improved parasite clearance thus suggesting that indeed L. sigmodontis actively suppresses the immune response to itself (26)(27)(28). The power of this suppression was demonstrated by the fact that implantation of a single L. sigmodontis female adult into resistant DBA/1 mice inhibited the clearance of MF, which under normal circumstances occurs within 3 d in this mouse strain (29).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The interference with regulatory T cell function in L. sigmodontis-infected BALB/c mice led to improved parasite clearance thus suggesting that indeed L. sigmodontis actively suppresses the immune response to itself (26)(27)(28). The power of this suppression was demonstrated by the fact that implantation of a single L. sigmodontis female adult into resistant DBA/1 mice inhibited the clearance of MF, which under normal circumstances occurs within 3 d in this mouse strain (29).…”
mentioning
confidence: 87%
“…It is, however, conceivable that resident Treg had initiated suppressive circuits in the very beginning of the infection. Taylor et al (28) showed that depletion of Treg before infection with L. sigmodontis reduced worm burden 60 d later, whereas Treg depletion by application of anti-CD25 mAb alone at later time points of infection did not improve resistance (26,27). In this setting, it was necessary to additionally interfere with other regulatory pathways by application of anti-CTLA-4 (27) or anti-GITR mAb (26) to improve resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the chances of survival, parasitic worms have evolved to exploit this Achilles' heel of the immune system by promoting the induction and expansion of Treg responses that result in downregulation of Th2 effector responses against the parasites (reviewed in [2,3]). The importance of this mechanism for the survival of the parasite is exemplified by the fact that, after depletion of Treg or neutralization of their suppressor molecules, Th2 immunity and protection against the infection can be restored [121][122][123]. Although Treg responses are beneficial to the parasite, the promotion of this regulatory arm is thought to be important for the host as well, since in several helminth models IL-10-deficient mice display severe pathology and increased mortality as a result of an overt inflammatory response to the parasitic infection [124][125][126].…”
Section: The Origin Of and Need For Treg Responsesmentioning
confidence: 99%
“…También se ha demostrado que los Treg inducidos por parásitos tienen capacidad inmunosupresora sobre otras poblaciones de linfocitos T (14). La secreción de IL-10 o TGF-β es un mecanismo inmunorregulador preponderante en algunas infecciones, al igual que la expresión de moléculas, como el antígeno 4 del linfocito T citotóxico (CTLA-4) o el miembro 19 de la superfamilia del receptor de factor de necrosis tumoral (GITR), que actúan mediante el contacto célula-célula (15,16).…”
Section: Linfocitos T Reguladoresunclassified